Potential of Water Spinach (Ipomea aquatica Forsk.) as A Phytoremediator of Household Water Waste in Geger Arum - Hardhaneszha, Azkaifa Syawqie; Hanieyane, Dendu Noutera Pramayuditya; Halisa, Halisa; Rabani, Naila Aulia; Surakusumah, Wahyu (Universitas Pendidikan Indonesia and Konsorsium Biologi Indonesia, 2025)
Household waste is one of the significant sources of environmental pollution in various urban areas, including in the waters of Geger Arum Area, Bandung. The use of water spinach (Ipomea aquatica Forsk.) for phytoremediation of household waste is an environmentally friendly and potentially effective alternative. This research aims to investigate the potential of Ipomoea aquatica Forsk. in phytoremediation of household waste. The method employed is a Completely Randomized Design experiment by testing Ipomoea aquatica plants to improve the quality of household wastewater. Treatments given include dilution of waste by 25%, 50%, and 75%. Based on statistical tests, physical and chemical parameters have a significant effect on the quality of household liquid waste. The results showed that the most optimum treatment was the treatment with 50%. dilution. Thus, the application of phytoremediation using water spinach has the potential to be a solution to overcome pollution of household wastewaters.